2017
DOI: 10.3390/nu9010031
|View full text |Cite
|
Sign up to set email alerts
|

Casein Glycomacropeptide Hydrolysates Exert Cytoprotective Effect against Cellular Oxidative Stress by Up-Regulating HO-1 Expression in HepG2 Cells

Abstract: Oxidative stress is considered as an important mediator in the progression of metabolic disorders. The objective of this study was to investigate the potential hepatoprotective effects and mechanisms of bovine casein glycomacropeptide hydrolysates (GHP) on hydrogen peroxide (H2O2)-induced oxidative damage in HepG2 cells. Results showed that GHP significantly blocked H2O2-induced intracellular reactive oxygen species (ROS) generation and cell viability reduction in a dose-dependent manner. Further, GHP concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…HO-1 gene expression has been shown to be regulated at the transcriptional level and enhanced by Nrf2 nuclear translocation [12,13,14], resulting from the activation of various signal transduction pathways, including extracellular signal-regulated kinase (ERK) and protein kinase B (PKB, Akt). HO-1 pla ys an important role in cytoprotection against oxidative damage [15,16,17]. In addition, HO-1 provides cytoprotection against ROS in the skin [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…HO-1 gene expression has been shown to be regulated at the transcriptional level and enhanced by Nrf2 nuclear translocation [12,13,14], resulting from the activation of various signal transduction pathways, including extracellular signal-regulated kinase (ERK) and protein kinase B (PKB, Akt). HO-1 pla ys an important role in cytoprotection against oxidative damage [15,16,17]. In addition, HO-1 provides cytoprotection against ROS in the skin [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been indicated that antioxidants may exhibit their antioxidant activity not by directly scavenging intracellular oxidants, but by inducing the endogenous antioxidant defense system (30). Activation of the antioxidant system is known to serve a significant role in cellular defense against oxidative impacts; detoxifying enzymes, including HO-1 and NQO1, which are regulated by Nrf2, are important parts of the system (4).…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 is an antioxidant and phase II detoxification enzyme that plays an important role in maintaining antioxidant homeostasis. It is present in most cells and tissues and is a key molecule for the adaptive cellular response in oxidative stress conditions [ 33 , 41 ]. Our results indicated that MCEE pretreatment positively affected the maintenance of antioxidant homeostasis through the upregulation of HO-1.…”
Section: Discussionmentioning
confidence: 99%